Unraveling the Influence of Soil Properties on CSR Strategies in an Ironstone Montane Ecosystem in Southeast Brazil - Paiva, Dario C.; Negreiros, Daniel; Cunha‐Blum, Jessica; Rago, Carla; Gomes, Vanessa M.; Gélvez‐Zúñiga, Irene [UNESP]; Fernandes, G. Wilson (Wiley, 2025)
ABSTRACT Question Understanding how nutrient availability and soil conditions influence ecosystem functionality is crucial for predicting changes in the plant community and informing ecological restoration programs. Here, we aimed to characterize the ecological strategies of the most abundant species in an ironstone ecosystem, to understand how edaphic parameters drive these strategies, and to investigate how species taxonomic, functional, and phylogenetic diversities differ among habitats within the ecosystem. Location The study was conducted in three municipalities in the southern portion of the Espinhaço mountain range in Minas Gerais, Brazil. We sampled plots in three habitat types with distinct soil characteristics. Methods We employed the CSR framework to characterize the ecological strategies of the most common species across 87,100‐m 2 plots. We also measured 19 edaphic parameters in these plots to evaluate their influence on ecological strategies. Results Most of the 46 sampled species displayed a high proportion of stress‐tolerant strategies due to their small leaves with high dry matter content. This pattern reflects the preponderance of S‐selection at the plot level. Conversely, plots with finer sand and relatively fertile conditions had more competitive strategies, and the species within showed larger leaves with less biomass investment. Conclusions This study highlights the role of abiotic filters in shaping CSR strategies in ironstone campo rupestre , emphasizing the trade‐off between growth and resource conservation. The low growth rates of species reveal the ecosystem's vulnerability to increased soil removal and disturbances. Additionally, small‐scale edaphic variation relates mainly to physical properties, selected species composition, and functionality.